2018
DOI: 10.1088/1748-605x/aaaa77
|View full text |Cite
|
Sign up to set email alerts
|

Guggulsterone-releasing microspheres direct the differentiation of human induced pluripotent stem cells into neural phenotypes

Abstract: Parkinson's disease (PD), a common neurodegenerative disorder, results from the loss of motor function when dopaminergic neurons (DNs) in the brain selectively degenerate. While pluripotent stem cells (PSCs) show promise for generating replacement neurons, current protocols for generating terminally differentiated DNs require a complicated cocktail of factors. Recent work demonstrated that a naturally occurring steroid called guggulsterone effectively differentiated PSCs into DNs, simplifying this process. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…Scanning electron microscopy showed that puro‐encapsulated microspheres possessed an average diameter of 3.4 ± 1.17 µm and exhibited a smooth rounded morphology ( Figure 1 a) similar to unloaded microspheres (average diameter previously reported as 2.24 ± 2.04 µm) (Figure b) . The size distribution for the puro‐loaded microspheres is shown in Figure c.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Scanning electron microscopy showed that puro‐encapsulated microspheres possessed an average diameter of 3.4 ± 1.17 µm and exhibited a smooth rounded morphology ( Figure 1 a) similar to unloaded microspheres (average diameter previously reported as 2.24 ± 2.04 µm) (Figure b) . The size distribution for the puro‐loaded microspheres is shown in Figure c.…”
Section: Resultssupporting
confidence: 52%
“…Compared to previous methods, this protocol avoids selection steps and allows for the sustained release of puro, lowering the amount of drug required. The EE of puro into the microspheres (84%) was higher than previously reported of other encapsulated drugs like RA (60.0%) and guggulsterone (42.4%), and similar to Clonazepam (72.6–95.1%) and tamoxifen . The average microsphere diameter size was 3.4 ± 1.17 µm, similar in size to unloaded and RA‐loaded microspheres with diameters of 2.24 ± 1.04 µm and 3.59 ± 2.48 µm, respectively .…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Integration of more mature neurons into the existing circuitry could have beneficial effects on behavioural outcomes. Agbay et al followed early reports that guggulsterone can promote differentiation of pluripotent stem cells into dopaminergic neurons and encapsulated the drug into poly-ε-caprolactone (PCL) microparticles, realising it over 44 days in vitro [5]. Guggulsterone microspheres promoted the highest levels of TUJ1 expression in human pluripotent stem-cell derived aggregates, suggesting that co-delivery of guggulsterone microspheres and stem cells could be a potential treatment strategy for Parkinson's disease.…”
mentioning
confidence: 99%